2003
DOI: 10.1007/s00170-002-1431-y
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Heat Effect in Excimer Laser Ablation of Polymer PC and ABS

Abstract: Analysis of the thermal effect and machining properties of PC (polycarbonate) and ABS (polyacrylonitrilebutadienestyrene) polymers when ablated using a KrF excimer laser is described. PC has less thermal effect on the geometric distortion than ABS in laser ablation. The cumulative heat during laser ablation results in geometric deformation in ABS micromachining. The number of laser pulses generates a greater geometric deformation in ABS than in PC according to experimental laser ablation observations. The PC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Examination of the graph showed that there are two distinctive regions, both of which require different interpretations. This curve is similar, but converse to that reported for Excimer laser ablation of ABS (Acrylonitrile butadiene styrene) polymer, in which the graph showed a maximum rather than a minimum [18]. The two regions are thought to correspond to different ablation mechanisms: in the first region, an increase in frequency led to a reduction in ablation as incident pulses which were in excess of those required to cause ablation of the polymer were absorbed by the ablated material and surroundings and thus converted to heat energy.…”
Section: (B) Uv Nd:yag Laser Ablation Of Optical Waveguidessupporting
confidence: 86%
“…Examination of the graph showed that there are two distinctive regions, both of which require different interpretations. This curve is similar, but converse to that reported for Excimer laser ablation of ABS (Acrylonitrile butadiene styrene) polymer, in which the graph showed a maximum rather than a minimum [18]. The two regions are thought to correspond to different ablation mechanisms: in the first region, an increase in frequency led to a reduction in ablation as incident pulses which were in excess of those required to cause ablation of the polymer were absorbed by the ablated material and surroundings and thus converted to heat energy.…”
Section: (B) Uv Nd:yag Laser Ablation Of Optical Waveguidessupporting
confidence: 86%
“…They are also characterized by higher etch rate, strong absorption by the material, improved surface roughness and lower ablation thresholds [Li, L., et al, 2011;Sugioka, et al, 2003]. These aforementioned features of the excimer laser have attracted and favoured its use not only for polymers [Wei & Yang, 2003] but also with other materials such as ceramics [Ihlemann, 1996], glasses [Tseng, et al, 2007] and silicon [Li, J. & Ananthasuresh, 2001] which are often hard to machine.…”
Section: Industrial Laser -Excimermentioning
confidence: 99%
“…Before applying the laser post processing, we analyzed the interaction characteristics of laser and ABS to determine the suitability of the laser technology. We also analyzed laser conditions suitable for post-processing [27,28]. The interaction characteristics using four different surface conditions are compared and analyzed.…”
Section: Introductionmentioning
confidence: 99%